The Role of Video-Assisted Thoracoscopic Surgery in Pediatric Oncology: Single-Center Experience and Review of the Literature - Riccipetitoni, Giovanna; Bertozzi, Mirko; Gazzaneo, Marta; Raffaele, Alessandro; Vatta, Fabrizio (Frontiers in Pediatrics, 2021)
Aim Video-assisted thoracoscopic surgery (VATS) has been widely used in the last decades. Nevertheless, the pros and cons of thoracoscopy versus open surgery in pediatric oncology are still under debate. In literature, VATS has been applied for both diagnostic and ablative surgery to treat neurogenic tumors, thymic neoplasms, lung tumors and metastases, germ cells tumors, lymphoproliferative diseases, and other rare tumors. Recent reviews described excellent outcomes in pediatric oncology as well as in the treatment of adult lung cancer, with a significantly higher rate of mortality and complication in thoracotomy compared to VATS. We reviewed our experience on thoracoscopy in pediatric malignancy and compared it to the literature. Materials and Methods Retrospective cohort-study of pediatric oncological patients who underwent VATS at our Institution from 2007 to 2020. Review of the recent literature on the topic. Results A total of 43 procedures were performed on 38 oncological patients (18 males, 20 females). Median age was years 7.72 (0.35-18.6). Diagnosis: 10 neurogenic tumors, 9 hematological diseases, 5 metastases, 4 lypoblastomas, 3 thymic pathologies, 3 germ-cell tumors, 2 pleuropneumoblastomas, 2 myofibroblastic tumors, 1 myoepithelial carcinoma, 1 liposarcoma, and 3 suspected oncological mass. In three cases, a 3D-model was elaborated to better plan the surgical approach. Diagnostic biopsies were 22(51.1%), ablative surgeries 21(48.9%). One neurogenic tumor was resected with the Da Vinci Robot. Median operative time was 120 minutes(30-420). A drain was left in place in 20 (46.5%) for a median of 4 days. Median length of hospitalization was 5 days(1-18). One case (2.3%) was converted (intra-operative bleeding). Three post-operative complications (7.0%): one pneumonia, one pleural effusion, and one diaphragmatic paralysis (need for plication). Results were compared to recent literature, morbidity, and conversion rate resulted comparable to reviewed publications. Conclusion VATS represents a valuable tool for diagnostic and therapeutic procedures in pediatric oncology. Nonetheless, it is a challenging technique that should be performed by expert surgeons on oncological and mini-invasive surgery. 3D reconstruction can optimize the pre-operative planning and guarantee a safer and more targeted treatment. Finally, the advent of robotic-assisted surgery represents a new challenge that may further implement the advantages of VATS.